EXTRAMURAL ENGLISH AND ADULT EFL LEARNERS’ PHONOLOGICAL AWARENESS - Sa'adah, Lailatus; Anam, Syafi'ul; Hentasmaka, Daning (Premise: Journal of English Education and Applied Linguistics, 2023)
This study examines the duration of adult EFL learners’ extramural English activities related to their phonological awareness. For this purpose, (Indonesian, N = 32, 3 males and 29 females) learners participated in the study. After analyzing the questionnaires and the phonological awareness test using the non-parametric (Spearman) correlation, the result showed a strong positive correlation between the amount of time the adult EFL learners spend for spoken and written extramural English activities and their phonological awareness ability. The extramural English activities they mainly engage in are dealing with technology. The findings call for future research examining the effect of extramural English on phonological awareness and other possible English components or skills.